2009
DOI: 10.1108/13522750910963809
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effects of different reward programs on in‐role and extra‐role performance of retail sales associates

Abstract: PurposeThe purpose of this paper is to explore the effects of different reward programs on in‐role and extra‐role behaviour; and to investigate whether specific reward programs can be designed to enhance both in‐role and extra‐role behaviour simultaneously.Design/methodology/approachSemi‐structured in‐depth interviews were conducted on a total of 11 employees from four different fashion retail outlets. Informants consisted of employees from different positions within these organizations (i.e. store manager, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 42 publications
0
2
0
3
Order By: Relevance
“…(Zhou et al, 2011). In addition, researchers such as Yap et al (2009) found that reward systems have a positive impact on employee performance. Although rewarding employees can be based on one or more factors such as performance, experience, qualification, and seniority (Lim & Ling, 2012), the most dominant factor used in organizations is performance where employees' performance is linked to expected rewards (Zaitouni et al, 2011;Vlachos, 2009).…”
Section: Reward Systemsmentioning
confidence: 99%
“…(Zhou et al, 2011). In addition, researchers such as Yap et al (2009) found that reward systems have a positive impact on employee performance. Although rewarding employees can be based on one or more factors such as performance, experience, qualification, and seniority (Lim & Ling, 2012), the most dominant factor used in organizations is performance where employees' performance is linked to expected rewards (Zaitouni et al, 2011;Vlachos, 2009).…”
Section: Reward Systemsmentioning
confidence: 99%
“…IRP involves core task behavior that directly or indirectly contributes to the individual and organizational productivity (Rich et al, 2010). As extra-role behaviors are discretionary, it means such behaviors go above and beyond the formal role requirements and are not specified in job descriptions (Yap et al, 2009). Because PCSP is a Family incivility typical extra-role performance not included in FLEs' job requirements, those who fail to exhibit beneficial proactive behaviors will not be punished (Lau et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Άτυπη αποζημίωση/ αμοιβή: ο προϊστάμενος ενός τμήματος ή η διεύθυνση ενός υποκαταστήματος του ίδιου οργανισμού βάσει ατομικού, ανεξάρτητου και αυθόρμητου σχεδιασμού καθορίζει το μείγμα των αμοιβών. (En Yap, Bove & Beverland, 2009) Αποτελεσματικό σε σχέση με το κόστος που γεννά για τον οργανισμό (Armstrong, Brown & Reilly, 2011) Αποκινητροποίηση-η επιβράβευση ενός συγκεκριμένου έργου μπορεί να δημιουργήσει απέχθεια για την επίτευξη ενός άλλου. (Alexy & Leitner , 2011) Ευπροσάρμοστη αμοιβή-πρέπει να προσαρμόζεται στις ιδιαίτερες ανάγκες του οργανωτικού περιβάλλοντος.…”
Section: πίνακας 64: δομικά στοιχεία ενός αποτελεσματικού συστήματος αμοιβών σε σχέση με τον παράγοντα αποζημίωση/αμοιβήunclassified
“…Οι En Yap, Bove & Beverland (2009), σε σχέση με την ύπαρξη πολλαπλών αυτόνομων υποσυστημάτων διανομής αμοιβών στο εσωτερικό ενός οργανισμού, υποστηρίζουν την ύπαρξη του σκέλους της τυπικής αποζημίωσης/αμοιβής και του σκέλους της άτυπης αποζημίωσης/ αμοιβής (formal and informal reward). Το σκέλος της τυπικής αποζημίωσης/ αμοιβής συνδέεται με την κεντρική διεύθυνση ενός οργανισμού, η οποία καθορίζει το μείγμα των αμοιβών που θα δοθούν στους εργαζόμενους.…”
unclassified
See 1 more Smart Citation